Análise de metais potencialmente tóxicos em ambientes aquáticos (Da Água e dos insetos da ordem Odonata) para biomonitoramento ambiental. - Ribeiro, Simone Maria (2019)
Potentially toxic metals are among the most common contaminants in waters and their origin may be both natural and anthropogenic. As soon as they come into contact with the aquatic ecosystem, the metals can be transported to the various compartments of the environment, such as soil, sediment, plants and animals, and may become bioaccumulative. With the increase of activities of anthropic origin and the degradation of water resources, biomonitoring becomes an effective way to expose various types of stress that may occur in the environment, serving as an alarm for declines in the quality of the environment and populations. With the determination of the adverse effects of the presence of contaminants in water bodies, it is becoming increasingly important to indicate environmental disturbances from possible contaminating sources such as agriculture. The objective of this study was to determine the levels of Zn2+, Cd2+, Cu2+, Co2+, Pb2+, Cr2+, Mn2+, Al3+ in the water and larvae of the order Odonata in dams 1 and 2, related to the conventional and organic planting of a plantation orange. The collected samples were previously digested and subjected to the analysis of determination of the potentially toxic metals using the atomic emission spectrometry equipment with microwave plasma (MP-AES). The water samples indicated for some metals a concentration above the limit allowed by CONAMA Resolution n° 357/2005, in the following order Cu2+> Pb2+> Mn2+ in both dams near conventional and organic cultivation. Cr ions were observed only in dam 1 (close to conventional planting) and Al ions in dam 2 (close to organic planting). In the Odonata larvae, the presence of metals Zn2+> Cu2+> Pb2+> Mn2+ was observed in both dams close to conventional and organic cultivation. All other metals were found in dams and larvae, even in small concentrations. It is concluded that the insects of the order Odonata absorb considerable concentrations of metals in the organism, the metals found in the Odonata resemble the metals found in the water, and it can be reinforced the concept that the Odonata are important indicators to monitor contaminations of metals in agricultural areas.